2001
DOI: 10.1002/1097-4598(200101)24:1<138::aid-mus22>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Myopathy with muscle spindle excess: A new congenital neuromuscular syndrome?

Abstract: An infant presented with congenital weakness, hypotonia, arthrogryposis, atrial tachycardia, and a left intra‐abdominal neuroblastoma. Muscle biopsy revealed marked excess of muscle spindles with atrophy of extrafusal fibers. The patient expired at age 14 months from progressive cardiorespiratory failure. Postmortem examination demonstrated muscle‐spindle excess in other muscles, along with hypertrophic obstructive cardiomyopathy and organomegaly. Muscle spindle excess has previously been reported in two patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Muscle biopsies from CS individuals have shown excess muscle spindles (Burgt, 2007;de Boode et al, 1996;Selcen et al, 2001), and we reported that skeletal muscle biopsies from CS patients showed excessively small skeletal muscle fibers with a type 2 myofiber predominance (Tidyman et al, 2011).…”
Section: Introductionmentioning
confidence: 72%
“…Muscle biopsies from CS individuals have shown excess muscle spindles (Burgt, 2007;de Boode et al, 1996;Selcen et al, 2001), and we reported that skeletal muscle biopsies from CS patients showed excessively small skeletal muscle fibers with a type 2 myofiber predominance (Tidyman et al, 2011).…”
Section: Introductionmentioning
confidence: 72%
“…It is difficult to discern if this is due to activity levels, limitations of movement either from central or peripheral neuropathies, or a primary myopathy. However, several individuals with Costello syndrome have been reported with weakness and an increased density of muscle spindles were shown in skeletal muscle biopsies in five individuals in which creatine kinase concentrations were normal and electromyogram measurements normal except for one individual with a myopathic pattern [de Boode et al, 1996; Selcen et al, 2001; Stassou et al, 2005; van der Burgt et al, 2007].…”
Section: Musculoskeletal Overlapmentioning
confidence: 99%
“…The link between skeletal myopathy and RASopathies first emerged from early case reports on hypotonic infants with CS- or NS-like clinical features. Skeletal muscle biopsies from these patients revealed an increase in the number of intrafusal muscle fibers ( Box 1 ), or muscle spindles ( Box 1 ), and the presence, in most, of small, atrophic, extrafusal muscle fibers ( de Boode et al, 1996 ; Selcen et al, 2001 ; Stassou et al, 2005 ; van der Burgt et al, 2007 ). These histological findings, together with the weakened muscles observed in patients upon clinical examination, led to a more detailed, systematic examination of skeletal muscle in patients with RASopathy, including assessment of muscle biopsies obtained from a cohort of patients aged 11 weeks to 8 years with a molecular diagnosis of CS or CFC ( Tidyman et al, 2011 ).…”
Section: Skeletal Muscle Histology In Rasopathiesmentioning
confidence: 99%